2018
DOI: 10.1016/j.bbrc.2018.04.109
|View full text |Cite|
|
Sign up to set email alerts
|

Long noncoding RNA HAGLROS regulates cell apoptosis and autophagy in lipopolysaccharides-induced WI-38 cells via modulating miR-100/NF-κB axis

Abstract: Pneumonia is a lower respiratory disease caused by pathogens or other factors. This study aimed to explore the roles and mechanism of long noncoding RNA HAGLROS in lipopolysaccharides (LPS)-induced inflammatory injury in pneumonia. The HAGLROS expression in serum of patients with acute stage pneumonia was detected. To induce pulmonary injury, WI-38 human lung fibroblasts were stimulated with lipopolysaccharides (LPS). The HAGLROS expressions in LPS-treated WI-38 cells and the effects of HAGLROS knockdown on th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
43
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 51 publications
(49 citation statements)
references
References 21 publications
5
43
0
1
Order By: Relevance
“…The release of inflammatory factors, such as TNF‐α, could promote cell apoptosis, microvascular dysfunction, and tissue necrosis . The cumulative message of several recent studies has revealed that lncRNAs are abnormally involved in inflammation response and serve as effective therapeutic targets for pneumonia . We put forward biological functions and mechanisms of XIST in pneumonia and firstly found that XIST knockdown lead to the inhibition of cell apoptosis and inflammation injuries in LPS‐induced WI‐38 cells by sponging miR‐370‐3p.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The release of inflammatory factors, such as TNF‐α, could promote cell apoptosis, microvascular dysfunction, and tissue necrosis . The cumulative message of several recent studies has revealed that lncRNAs are abnormally involved in inflammation response and serve as effective therapeutic targets for pneumonia . We put forward biological functions and mechanisms of XIST in pneumonia and firstly found that XIST knockdown lead to the inhibition of cell apoptosis and inflammation injuries in LPS‐induced WI‐38 cells by sponging miR‐370‐3p.…”
Section: Discussionmentioning
confidence: 99%
“…Cells (2 × 10 5 ) were plated in 6‐well plates and incubated 24 hours. LPS in different concentrations (5, 10, and 20 μg/mL) was added in medium for 12 hours to establish injury model …”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The reported target genes of hsa-miR-100-5p include polo-like kinase 1 [21,32], insulin-like growth factor (IGF) [33], IGF-1 receptor [34], mammallian target of rapamycin (mTOR) [34], fibroblast growth factor receptor 3 [35], ataxia telangiectasia mutated (ATM) [36], Argonaute 2 [37], isoprenylcysteine carboxyl methyltransferase (ICMT) [38], nuclear factor-κB3 [39], rasrelated C3 botulinum toxin substrate 1 (Rac1) [38], and β-tubulin [40].…”
Section: Discussionmentioning
confidence: 99%
“…Long noncoding RNAs (lncRNAs) play critical roles in a variety of human diseases including pneumonia (Huang et al, ; M. Liu, Han, Shi, & Chen, ). LncRNA growth arrest‐specific 5 (GAS5) has been demonstrated to have a role in macrophage polarization (Simion, Haemmig, & Feinberg, ).…”
Section: Introductionmentioning
confidence: 99%